The Role of Islamic Counseling and Guidance in Augmenting Resilience in Adolescents at Madrasah Aliyah Muslimat Nahdlatul Ulama Palangka Raya City - Nanda Ila Aulia Zulaekah; Ali Sibram Malisi; Nor Fatmah (Istisyarah: Jurnal Bimbingan Konseling Islam, 2025)
This study aims to analyse the effectiveness of Islamic counseling guidance in enhancing adolescent resilience at Madrasah Aliyah Muslimat Nahdlatul Ulama in Palangka Raya. Resilience refers to an individual's ability to adapt and recover from life's challenges. In the educational context, resilience is crucial for adolescents to cope with academic pressures, social conflicts, and emotional changes. This research employs a qualitative approach with a descriptive method. Data were collected through interviews, observations, and documentation. The findings indicate that Islamic counseling guidance, which is based on Islamic values such as patience, sincerity, and reliance on Allah, plays a significant role in strengthening adolescents' psychological and spiritual resilience.